1990
DOI: 10.1021/jm00163a016
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization-activated prodrugs. Basic carbamates of 4-hydroxyanisole

Abstract: A series of basic carbamates of 4-hydroxyanisole was prepared and evaluated as progenitors of this melanocytotoxic phenol. All of the carbamates were relatively stable at low pH but released 4-hydroxyanisole cleanly at pH 7.4 at rates that were structure dependent. A detailed study of the N-methyl-N-[2-(methylamino)ethyl]carbamate showed that generation of the parent phenol followed first-order kinetics with t1/2 = 36.3 min at pH 7.4, 37 degrees C, and was accompanied by formation of N,N'-dimethylimidazolidino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 6 publications
(8 reference statements)
2
78
0
3
Order By: Relevance
“…A classical example is that of aminocarbamate prodrugs 9 of 4-hydroxyanisole, prepared by Saari et al, who found them to release the parent compound by intramolecular cyclization of the carrier moieties to imidazolidin-2-ones 10 (Scheme 7) and not to be susceptible to murine plasma esterases [25]. All the compounds tested were stable at low pH but were reactive in neutral and alkaline medium, releasing 4-hydroxyanisole at rates that were structure dependent (t 1/2 ranging from 36 to 942 min, at pH 7.4 and 37 ºC).…”
Section: General Basic Amine Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…A classical example is that of aminocarbamate prodrugs 9 of 4-hydroxyanisole, prepared by Saari et al, who found them to release the parent compound by intramolecular cyclization of the carrier moieties to imidazolidin-2-ones 10 (Scheme 7) and not to be susceptible to murine plasma esterases [25]. All the compounds tested were stable at low pH but were reactive in neutral and alkaline medium, releasing 4-hydroxyanisole at rates that were structure dependent (t 1/2 ranging from 36 to 942 min, at pH 7.4 and 37 ºC).…”
Section: General Basic Amine Carriersmentioning
confidence: 99%
“…This implies that, for n>3, intramolecular activation is unlikely to increase reaction rates. In what concerns the introduction of Nmethyl (R 1 , R 2 , R 3 ) or N-ethyl substituents (R 1 , R 2 ), di-and tri-methyl derivatives were more reactive than their unsubstituted, mono-methyl and di-ethyl counterparts [25]. Scheme 7.…”
Section: General Basic Amine Carriersmentioning
confidence: 99%
“…N-Boc-aminopropoxy quinolinecarboxamide 5 was carried out the O-alkylation of quinolinecarboxamide 3 with N-Boc-3-bromopropoxyamine using K 2 CO 3 in refluxing acetonitrile, 15 followed by the treatment with 2 M HCl etherate 16 generating aminopropoxy quinolinecarboxamide salt 6 in 93 % overall yield. It should be noted that the solubility of quinolinecarboxamide 3 was transformated from organic solubility to the enhanced aqueous solubility for the pharmacological assay.…”
Section: Resultsmentioning
confidence: 99%
“…This sequence of reactions within the trigger portion of the molecule generates, on decarboxylation, a free amine in the spacer element that undergoes a spontaneous 1, 5 cyclization to release free drug and N,N-dimethyl urea. The N,NЈ-dimethyl-substituted ethylenediamine spacer was chosen because it provides for a more rapid cyclization reaction than the unsubstituted spacer (20).…”
Section: Resultsmentioning
confidence: 99%